2009
DOI: 10.1002/cd.243
|View full text |Cite
|
Sign up to set email alerts
|

How social and cultural contexts shape the development of coping: Youth in the inner city as an example

Abstract: Because the patterns of coping shown by children and youth depend on the particular types and levels of stress they face, it is difficult to understand or study coping, or to promote it in interventions, unless coping is conceptualized as embedded within the overall ecology of stressful conditions, including the demands and resources that influence the use, utility, and impact of coping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 36 publications
2
35
0
Order By: Relevance
“…For example, Tolan and Grant (2009) described the broader community socialization context around the development of children's coping styles; Kliewer and colleagues (e.g., Kliewer et al, 2006) have similarly identified the critical importance of parental socialization of children's coping. It might be the case that overarching socioeconomic and family contextual influences under distressed conditions promote similar patterns of coping across different stressors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Tolan and Grant (2009) described the broader community socialization context around the development of children's coping styles; Kliewer and colleagues (e.g., Kliewer et al, 2006) have similarly identified the critical importance of parental socialization of children's coping. It might be the case that overarching socioeconomic and family contextual influences under distressed conditions promote similar patterns of coping across different stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Coping reactions emitted in response to stressful or otherwise challenging events can be highly particular, emerging in the context of youths' construction of the controllability of the difficult event, the actual content and circumstances of the event itself, broader sociocultural factors, individual learning histories, and personal resources (Compas et al, 2001; Tolan & Grant, 2009). A number of studies thus support the key notion that how a youth responds situationally to a stressor is linked to relatively stable background factors as well as stress mobilization processes in which particular stressors elicit particular coping reactions, perhaps even idiosyncratically or in highly specific ways (Bjorck & Cohen, 1993; Dubow, Pargament, Boxer, & Tarakeshwar, 2000).…”
Section: Coping With Stress and Violencementioning
confidence: 99%
See 1 more Smart Citation
“…Those findings support the current research and may help partially explain why active coping was positively related to anxiety. Furthermore, Tolan & Grant, 2009 reports that there is little evidence to suggest that active coping is effective in reducing stress from uncontrollable events. Many of the negative life events experienced by low-income African Americans are those in which they have little or no control, such as exposure to community violence and experiencing a lack of basic needs (e.g., food, shelter) (Grant, O'Koon, Davis, Roache, & Poindexter, 2000).…”
Section: Copingmentioning
confidence: 96%
“…Social support has been suggested as a protective mechanism against burnout (Xanthopoulou, Bakker, Demerouti, et al, 2007). Research is beginning to recognise that coping is often a social process which derives from the social environment in which it occurs (Skinner & Beers, 2016;Tolan & Grant, 2009). Participants in a recent teacher study also raised the importance of social support in order to sustain a mindfulness practice (Schussler et al, 2016).…”
Section: Shared Experiencementioning
confidence: 99%